Ballistic impact behaviour of glass fibre reinforced polymer composite with 1D/2D nanomodified epoxy matrices. (15th June 2019) - Domun, Nadiim; Kaboglu, Cihan; Paton, Keith R.; Dear, John P.; Liu, Jun; Blackman, Bamber R.K.; Liaghat, Gholamhossein; Hadavinia, Homayoun
Abstract: In this paper, experimental studies on the ballistic impact behaviour of nanomodified glass fibre-reinforced polymer (GFRP) are reported. The epoxy matrix of the GFRP was modified by the addition of graphene platelets (GNPs), carbon nanotubes (CNTs), combined hybrid hexagonal boron nitride nanosheets (BNNS)/CNT, and combined boron nitride nanotubes (BNNTs)/GNPs nanoparticles. Ballistic impact tests were carried out on GFRP laminates at two projectile velocities of 76 ± 1 m s −1 for full-field deformation measurements and 134.3 ± 1.7 m s −1 for perforation tests. The behaviour of the plates during impact was recorded using digital image correlation (DIC), in order to monitor strain and out-of-plane deformation in panels with nanoreinforced matrices. Following penetrative impact tests, pulse thermography was used to characterise the delamination of impacted plates. The results of full-field deformation, exit velocity and energy absorption measurements from the ballistic tests show significant improvements in impact resistance for the panels made from nanomodified epoxies relative to laminates with the unmodified epoxy matrix. The highest absolute absorbed energy was observed for the GFRP panels fabricated using the epoxy matrix loaded with BNNT/GNP at 255.7 J, 16.8% higher than the unmodified epoxy matrix.